Prediction of hamstring injuries in australian football using biceps femoris architectural risk factors derived from soccer - Dow, C. L.; Timmins, R. G.; Ruddy, J. D.; Williams, M. D.; Maniar, N.; Hickey, J. T.; Bourne, M. N.; Opar, D. A. (The American Journal of Sports Medicine, 2021)
Background: Hamstring strain injuries are the most common injuries in team sports. Biceps femoris long head architecture is associated with the risk of hamstring injury in soccer. To assess the overall predictive ability of architectural variables, risk factors need to be applied to and validated across different cohorts.